2020
DOI: 10.1074/jbc.ra119.010360
|View full text |Cite
|
Sign up to set email alerts
|

The dNTPase activity of SAMHD1 is important for its suppression of innate immune responses in differentiated monocytic cells

Abstract: Sterile alpha motif and HD domain-containing protein 1 (SAMHD1) is a deoxynucleoside triphosphohydrolase (dNTPase) with a nuclear localization signal (NLS). SAMHD1 suppresses innate immune responses to viral infection and inflammatory stimuli by inhibiting the NF-κB and type I interferon (IFN-I) pathways. However, whether the dNTPase activity and nuclear localization of SAMHD1 are required for its suppression of innate immunity remains unknown. Here, we report that the dNTPase activity, but not nuclear localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 44 publications
3
28
0
Order By: Relevance
“…Our studies were carried out in the absence of these viral components, which raises the possibility that viral proteins may also counteract SAMHD1-suppression of NF-κB in order to maintain HIV-1 replication. Furthermore, TRAF6 has been shown to regulate HIV-1 production in macrophages (57) Our current and previous results demonstrated that nuclear localization of SAMHD1 is dispensable for suppression of NF-κB activation in HEK293T cells and differentiated THP-1 or U937 monocytic cell lines (20). These observations support the notion that a cytoplasmic portion of SAMHD1 may specifically function to block proteins involved in NF-kB signaling, such as TRAF6/2, TAB3, and/or TAK1.…”
Section: Discussionsupporting
confidence: 80%
“…Our studies were carried out in the absence of these viral components, which raises the possibility that viral proteins may also counteract SAMHD1-suppression of NF-κB in order to maintain HIV-1 replication. Furthermore, TRAF6 has been shown to regulate HIV-1 production in macrophages (57) Our current and previous results demonstrated that nuclear localization of SAMHD1 is dispensable for suppression of NF-κB activation in HEK293T cells and differentiated THP-1 or U937 monocytic cell lines (20). These observations support the notion that a cytoplasmic portion of SAMHD1 may specifically function to block proteins involved in NF-kB signaling, such as TRAF6/2, TAB3, and/or TAK1.…”
Section: Discussionsupporting
confidence: 80%
“…TAK1 activation by IL-1β or stimulation of host pathogen recognition receptors (PRRs) depends on the recruitment of the upstream factor TRAF6, which catalyzes the formation of K63-linked polyubiquitin chains (33). Using a NLS-defective SAMHD1 mutant (mNLS), we have demonstrated that SAMHD1 inhibits IL-1β-induced NF-κB activation independently of its NLS (20). To determine if SAMHD1 suppress NF-κB activation initiated through TRAF6, we used an NF-κB-luciferase reporter plasmid system.…”
Section: Resultsmentioning
confidence: 99%
“…The pcDNA3-GFP vector was previously described (59). The pCG-FLAG-HA plasmids (60) encoding the SAMHD1 mutant NLS (mNLS) and the P275A mutants were generated using a QuikChange Site-Directed Mutagenesis Kit (Agilent Technologies) according to the manufacturer’s protocol using the following primers: 5’-GAG CAG CCC TCC GCG GCT CCC GCT TGC GAT GAC AGC (mNLS) (20) and 5’-GGA ACA AAT TGT AGG AGC ACT TGA ATC ACC TGT C (SAMHD1 P275A). The pCG-FLAG-HA-SAMHD1 plasmid was a kind gift from Dr. J. Skowronski.…”
Section: Methodsmentioning
confidence: 99%
“…As a nuclear localization sequence (NLS)-containing protein [46][47][48] (Figure 2), SAMHD1 has been suspected to maintain strict nuclear localization [9,49,50]. However, many studies have demonstrated that SAMHD1 can be partially cytosolic [46,51,52]-maintaining relatively equal nuclear and cytosolic populations in some cell types [53,54]-and that its localization varies due to the cellular environment. Upon oxidative stress, SAMHD1 was found to migrate from the nucleus to the cytoplasm, only to return back to the nucleus one hour after stimulation [43].…”
Section: Samhd1 Protein Contains An Nls and Is Expressed In A Varietymentioning
confidence: 99%